Persistent Pain: Physiotherapy Student Experiences of Person-Centred Care in Musculoskeletal Outpatient Departments - Claydon, Aneurin James; Paul-Taylor, Graeme (International Journal of Practice-based Learning in Health and Social Care, 2017)
Person-centred care is championed throughout healthcare and emphasised in the management of persistent pain. Research reports that physiotherapists and physiotherapy students have struggled to integrate person-centred care into their practice and clinical work with people experiencing persistent pain. The aim of the study was to explore physiotherapy students’ experiences of person-centred care with people with persistent pain in a musculoskeletal outpatients’ placement setting, and to understand what affects physiotherapy students’ ability to implement person-centred practice. An interpretive qualitative method was used with data being collected by semi-structured focus groups of a purposive sample of undergraduate final-year physiotherapy students. A thematic approach to data analysis was completed using a cyclical immersive process. Three themes emerged: understanding of person-centred care, learning, and influences on clinical practice. The students showed an understanding of person-centred care in line with current literature. Person-centred care was generally deemed ‘well taught’ at university however this did not translate into their practice in a placement setting. Several factors influenced their ability to implement person-centred care, and this impacted upon their learning and their management of people presenting with persistent pain. In conclusion, physiotherapy students struggled to integrate learning of person-centred care from university into their practice on a musculoskeletal outpatient’s placement. It is recommended that physiotherapy course teams consider their curricula so that university and placement teaching facilitate person-centred learning and improve the management of persistent pain.